AN EMPIRICAL STUDY OF THE TREND AND PATTERN OF VIDEO-FILM PIRACY IN NIGERIA - Ridwan, Adeyemi A.; Akashoro, Ganiyu; Ajaga, Mukaila (European Scientific Journal, ESJ, 2013)
Piracy is allegedly threatening the survival of the film and video industries worldwide, particularly in countries with developed film industries. Investors in the film industries have alleged that, video piracy has led to huge losses, thereby threatening their survival. Although, some studies have been conducted on the global trend of film and video piracy particularly on the situations in the United States of America, Britain, France and India among others, only few studies have been conducted on the video piracy phenomenon in Nigeria despite the fact that, the country has the second largest video industry in the world. Besides the studies on the Nigerian scenario being few, only one of such studies has been conducted from insider’s perspective. Consequently, the studies are not exhaustive, hence the need for an exhaustive empirical study on the trend and pattern of video piracy in Nigeria. This study’s main objective is to investigate and analyze the trend, pattern and dynamics of video piracy as it affects the Nigerian video industry. The qualitative design was adopted for the study, while the combined methods of in-depth interview, focus group discussion and documents analysis were used for data collection. A triangulation of the interpretive and critical analytical techniques were also adopted for the data analysis within the diffusion of innovation theoretical framework for this study which made the following findings that; the rate of video piracy in Nigeria is alarming and dangerous; that video pirates conduct their activities with sophisticated technology and high level criminality; that, video piracy trend has taken an endangering ethnic dimension capable of causing ethnic conflict between two major ethnic groups, (Yoruba and Igbo) in Nigeria. The prevalence of television and internet piracy as well as the multiple-in-one DVD piracy format also forms part of the major findings of this study. This study updates and enriches general knowledge on videography and video piracy phenomenon in particular.